A companion to public philosophy - McIntyre, Lee C.; McHugh, Nancy Arden; Olasov, Ian (Blackwell companions to philosophy., 2022)
"Will have appeal to a very diverse range of philosophers, across all traditional branches of philosophy (nearly all major areas are covered). Combines substantive philosophical work on the various philosophical areas, with detailed methodological work, and introductory chapters exploring the nature of public philosophy per se"--